First record of the genus Discotylenchus Siddiqi, 1980 (Nematoda: Tylenchidae) from Iran, with description of one new and data on two known species - Ghaemi, Razieh; Pourjam, Ebrahim; Atighi, Mohammad Reza; Pedram, Majid; Karssen, Gerrit (Zootaxa, 2012)
The genus Discotylenchus is reported for the first time from Iran. Discotylenchus iranicus n. sp. is described and illustratedbased on morphological and morphometric characters. The new species is characterized by a combination of the followingmorphological features: lip region continuous and smooth, tapering to an offset prominent labial disc, lateral field withfour incisures, stylet length of 14–15μm, vulva position at 70.8–76.5 %, tail length of 81–100μm, conoid with a roundedtip and presence of males. The Iranian population of D. brevicaudatus shows a wider morphometric range compared tothe original description and the male of this species is described for the first time. The morphological characters and range of morphometric data of D. discretus are in full agreement with the original population.